Physiological Responses of Workers' Vital Signs in High Temperature Environments at The Tofu Home Industry Kedung Tarukan Surabaya - Trias Budi Wisnu Hartono (JURNAL KESEHATAN LINGKUNGAN, 2019)
The workplace environment has an influence on the workers wellbeing condition, in relation to work activities. Heat pressure arises and causes a burden on the workers who work in high temperature environments. The tofu production process causes heat radiation in the workplace in the Kedung Tarukan Surabaya Tofu Home Industry, whereas almost all activities are carried out in the same location, so that it is likely that workers are exposed to heat continuously during work. The purpose of this study was to analyze the differences of physiological responses of vital signs on the workers in high temperature environments at the tofu home industry Kedung tarukan Surabaya. this study was an observational study with a cross-sectional study design. Data was analyzed statistically using Paired t-test, this study use total population of 14 workers. The results of high temperature measurement of the working area of the Tofu home Industry Kedung Tarukan Surabaya showed that the average value of Wet and Ball Temperature Index (ISBB) was 30,52oC. The workload was categorized as medium, with the workload range of 50% – 75% working hour with workloads in the medium category and 50-75% working time from 1 hour. The results of physiological conditions measurement of vital signs was significantly different (<α 0,05) between before and after work on systolic blood pressure (p = 0,045), pulse (p = 0,039), body temperature (p = 0,006) and respiratory rate (p = 0,014). Whereas there was no significant difference in diastolic blood pressure (p = 0,069). this study concludes that the temperature of the work environment in the tofu home industry Kedung Tarukan Surabaya exceeding the NAB (limit value), caused an extra burden on the workers. It should be clearly informed to the workforce community regarding the potential dangers of working in a high temperature environment. It is also crucial to provide health education about the minimum required liquid consumption needs, providing drinking water for workers, monitoring and managing health safety (K3) in the work environment, and regulating breaks period for workers.